Ecomorphological evaluation of the Łyna River along the Kotowo-Ardapy section - Grzybowski, Mirosław; Endler, Zbigniew (Quaestiones Geographicae, 2012)
The Water Framework Directive of the European Parliament and the European Union Council No 2000/60/EC, of 23rd October 2000, on the common water policy, modifies provisional rules of river monitoring. Being an EU country, Poland has been obliged to introduce the new regulations and, additionally, to elaborate and implement regional methods for hydromorphological assessment of quality of river water no later than 2006. In the present study, hydromorphological evaluation of the Łyna River along a 7-km-long section between Kortowo and Adrapy has been completed. Along this section, the Łyna is a lowland, gravel and highly natural river. Two methods of evaluation, based on different assumptions, were applied. One is a British method, called River Habitat Survey (RHS), whereas the other one is based on German methods, known as ecomorphological river evaluation, and has been developed by Ilnicki (University of Agriculture in Poznań). A comparative analysis of the usefulness of both methods was performed, based on the results obtained with each method. The scope of our study has been to include a survey of the flora, phytosociological relationships and fauna of the river and its environs. Both methods implied that the river was more natural upstream and the results are shown on maps. The ecomorphological river evaluation, according to Ilnicki, assesses the river along its entire course, which is in accord with the Directive's assumptions. In contrast, the RHS method, which analyses selected, 500-meter-long sections, results in a non-continuous river evaluation. I our study, the assessment by RHS led to the omission of the most valuable section of the river. However, RHS (owing to the HQA index) more accurately indicates anthropogenic influences on the river, unlike the ecomorphological evaluation by Ilnicki, which lacks such an index. Consequently, the estimation of the degree of naturalness or extent of man-made pressure is not free from some subjectivity, which means that the surveyor needs certain experience. The RHS method is objective and unambiguous but still needs adaptation to the Polish conditions. Both methods can be statistically elaborated. At present, it is difficult to compare the reliability of the results obtained by both methods. The RHS method requires an application of a reference group of rivers, which has not been prepared for Poland yet. Assuming that the RHS database on the examined rivers (the Department of Ecology and Environmental Protection, August Cieszkowski Agricultural University in Poznań) could correspond to that missing reference group for Polish rivers, the results obtained by both methods were comparable.